Discordance between humoral and cellular immune responses to cytomegalovirus infection in CMV seropositive patients awaiting lung transplantation - Boada-Pérez, Meritxell; Berastegui, Cristina; Erro, Marta; Ussetti, Piedad; Crespo, Elena; Donadeu, Laura; Bestard, Oriol; Anguera, Gabriel; Solé, Amparo; Ponz Mir, Ricardo; Molloy, Brian; Revilla-López, Eva; et al. (Frontiers in Immunology, 2025)
IntroductionRisk stratification for CMV infection in lung transplantation (LT) currently relies on determining donor and recipient CMV IgG before transplantation. However, it has been observed that some patients who test positive for CMV-specific humoral response before kidney transplantation (KT) exhibit a weak or absent CMV-specific cellular response. The significance of this observation in LT is still unknown.MethodsThis prospective, multicenter, observational study evaluated the agreement between CMV IgG serology and specific cell-mediated response (specific T cell Enzyme-Linked ImmunoSpot Assay, ELISPOT, against CMV pp65 and IE-1 antigens) in 121 patients on the waiting list for LT.ResultsOne hundred and four (86%) patients were seropositive for CMV. Discordant humoral and cellular immunologic responses were observed, 29% of seropositive patients had a weak ELISPOT response to IE-1 and 39% to pp65. In 22% of seropositive patients, there was a weak or no response to both antigens. All seronegative patients did not respond to either antigen.ConclusionsTherefore, over 20% of CMV seropositive LT candidates showed weak CMV-specific cellular immune responses despite detectable serological memory against CMV. This may be important in assessing the risk of developing a CMV infection after transplantation.